Analysis of Factors Affecting the Cost Performance of Road Improvement Work in Serang Regency - Gusbian, Tri; Amin, Mawardi (Universitas Ibn Khaldun Bogor, 2024)
The Road Infrastructure Development Acceleration Program that has been launched by the Serang Regency Government in the 2017 fiscal year to the 2021 fiscal year, In the implementation of road improvement work in Serang Regency, a working length of 100 kilometers per year has been set for 5 budget years starting from the 2017-2021 fiscal year, the implementation of road improvement work in Serang Regency until the end of 2021 the remaining 20 kilometers due to changes in road length and increase in the volume of work in the field. This study analyzes the factors of additional costs incurred on road improvement work in Serang Regency by identifying the factors causing the cost increase from the largest to smallest factors data collection methods through questionnaires and interviews addressed to contractor personnel with validity, reliability and correlation tests used for data processing, while descriptive analysis is used for data analysis using Jeffreys Amazing Statistics Program (JASP) version 0.16.2 and Relative Importance Index (RII) are expected with this method to determine the factors causing additional costs in road improvement work. The highest level factor was identified as causing the additional cost of implementing Serang Regency road improvement work, namely Volume Changes (Technical Factors) with an RII index value of 0.715.